2018
DOI: 10.1042/etls20180026
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal cell biology: diverse functions of tubulin-like cytoskeletal proteins at the cell envelope

Abstract: The tubulin superfamily of cytoskeletal proteins is widespread in all three domains of life — Archaea, Bacteria and Eukarya. Tubulins build the microtubules of the eukaryotic cytoskeleton, whereas members of the homologous FtsZ family construct the division ring in prokaryotes and some eukaryotic organelles. Their functions are relatively poorly understood in archaea, yet these microbes contain a remarkable diversity of tubulin superfamily proteins, including FtsZ for division, a newly described major family c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…E218A) from a plasmid in a wild-type genetic background and then observed cell shapes. The E218A mutation in the GTPase active site strongly inhibits CetZ1 function via hyperstabilization of localized polymers, and was used previously for verification of CetZ1's involvement in rod development in motility soft agar [4]. We found that expression of cetZ1.…”
Section: Requirement Of Tubulin-like Protein Cetz1 For Elongated Shapmentioning
confidence: 79%
See 4 more Smart Citations
“…E218A) from a plasmid in a wild-type genetic background and then observed cell shapes. The E218A mutation in the GTPase active site strongly inhibits CetZ1 function via hyperstabilization of localized polymers, and was used previously for verification of CetZ1's involvement in rod development in motility soft agar [4]. We found that expression of cetZ1.…”
Section: Requirement Of Tubulin-like Protein Cetz1 For Elongated Shapmentioning
confidence: 79%
“…To verify that CetZ1 function is necessary for rod and tubule formation, we expressed a dominant-inhibitory mutant (CetZ1.E218A) from a plasmid in a wild-type genetic background and then observed cell shapes. The E218A mutation in the GTPase active site strongly inhibits CetZ1 function via hyper-stabilization of localized polymers, and was used previously for verification of CetZ1’s involvement in rod development in motility soft agar [4]. We found that expression of cetZ1 .E218A blocked rod cell and tubule formation in the wild-type strain background (), confirming its dominant influence on cell shape and the requirement for functional CetZ1 in trace-element-induced rod and tubule generation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations